Surfactant BL-Induced Changes in Blood Gas Composition and Acid-Base Balance In Neonatal Respiratory Distress Syndrome - S. A. Perepelitsa; I. F. Ostreikov (Общая реаниматология, 2006)
The paper presents the results of a study of blood gas composition and acid-base balance (ABB) in the use of the Russian drug Surfactant BL in preterm neonatal infants with respiratory distress syndrome (RDS). The surfactant was given to 57 preterm neonates. A control group consisted of 52 children with RDS who had received a course of treatment before the use of the drug in the hospital. Statistical analysis indicated the virtual similarity of the study and control groups. The study demonstrated that that in Surfactant BL-treated patients, blood oxygenation (pO2, %SO2c, A-a DO2, respiratory coefficient) improved much more rapidly and the mean values of these parameters remained statistically significantly better from the end of 24 hours of treatment than in the control neonates up to the end of therapy in the intensive care unit of the maternity hospital. Studies of blood ABB showed that the neonates of both groups had moderate metabolic acidosis at the initiation of therapy. With the therapy performed, the parameters of ABB generally reached normal values within the first 24 hours of therapy. There were no obvious differences in the changes of blood ABB parameters in the neonatal infants of both groups. Analysis of the results of treatment in neonates with ABB showed a statistically significant advantage in terms of positive outcomes of treatment in the group of Surfactant BL-treated patients.